Crossing the wall - Faustino, Marisa M. (2021)
Bioelectrochemical systems (BES) are emerging as a suite of versatile sustainable technologies to produce electricity and added‐value compounds from renewable and carbon‐neutral sources using electroactive organisms. The incomplete knowledge on the molecular processes that allow electroactive organisms to exchange electrons with electrodes has prevented their real‐world implementation. In this manuscript we investigate the extracellular electron transfer processes performed by the thermophilic Gram‐positive bacteria belonging to the Thermincola genus, which were found to produce higher levels of current and tolerate higher temperatures in BES than mesophilic Gram‐negative bacteria. In our study, three multiheme c‐type cytochromes, Tfer_0070, Tfer_0075, and Tfer_1887, proposed to be involved in the extracellular electron transfer pathway of T. ferri-acetica, were cloned and over‐expressed in E. coli. Tfer_0070 (ImdcA) and Tfer_1887 (PdcA) were purified and biochemically characterized. The electrochemical characterization of these proteins supports a pathway of extracellular electron transfer via these two proteins. By contrast, Tfer_0075 (CwcA) could not be stabilized in solution, in agreement with its proposed insertion in the pepti-doglycan wall. However, based on the homology with the outer‐membrane cytochrome OmcS, a structural model for CwcA was developed, providing a molecular perspective into the mechanisms of electron transfer across the peptidoglycan layer in Thermincola.